2013
DOI: 10.1186/1742-4755-10-44
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco cessation intervention for pregnant women in Argentina and Uruguay: study protocol

Abstract: BackgroundArgentina and Uruguay are among the countries with the highest proportion of pregnant women who smoke. The implementation of an effective smoking cessation intervention would have a significant impact on the health of mothers and infants. The “5 A’s” (Ask, Advise, Assess, Assist, Arrange) is a strategy consisting of a brief cessation counseling session of 5–15 minutes delivered by a trained provider. The “5 A’s” is considered the standard of care worldwide; however, it is under used in Argentina and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…A survey conducted in 20 public maternity hospitals in Buenos Aires, Argentina, and Montevideo, Uruguay in 2010 showed that only 10% of smokers were receiving brief counseling during prenatal care. 9 A survey conducted in Argentina in 2005, showed that only 22% of obstetrician/gynaecologists had received training in cessation counseling and 48.5% reported insufficient knowledge to provide cessation advice. Although 88.9% consistently advised women to stop smoking, three out of four providers believed it was acceptable for pregnant women to smoke up to six cigarettes per day.…”
Section: Introductionmentioning
confidence: 99%
“…A survey conducted in 20 public maternity hospitals in Buenos Aires, Argentina, and Montevideo, Uruguay in 2010 showed that only 10% of smokers were receiving brief counseling during prenatal care. 9 A survey conducted in Argentina in 2005, showed that only 22% of obstetrician/gynaecologists had received training in cessation counseling and 48.5% reported insufficient knowledge to provide cessation advice. Although 88.9% consistently advised women to stop smoking, three out of four providers believed it was acceptable for pregnant women to smoke up to six cigarettes per day.…”
Section: Introductionmentioning
confidence: 99%
“…Except for clinic directors, a convenience sample for each segment was employed until reaching saturation. This research was conducted during August–November 2010 prior to implementing a randomized-cluster controlled trial [26]. …”
Section: Methodsmentioning
confidence: 99%
“…Women were eligible for the study if they attended one of 21 prenatal clinic clusters and delivered in one of 10 public hospitals in the Province of Buenos Aires, Argentina, or one of two hospitals in Montevideo, Uruguay, during October 2011–May 2012 (5). Within 12 h after delivery, trained interviewers asked eligible women two questions about their smoking status, and women who self-reported quitting smoking during pregnancy were asked to provide a saliva sample by chewing on the cotton swab insert from a Salivette ® (Sarstedt, Newton, NC, USA).…”
Section: Methodsmentioning
confidence: 99%